23 Feasibility assessment for the implementation of a virtual hypertrophic cardiomyopathy follow up clinic in a district general hospital. (4th June 2021) - Luo, Elton; Chan, Kenneth; Tilling, Lindsey; Balkhausen, Katrin; Bull, Sacha
Abstract : Background: The COVID-19 pandemic has presented unprecedented challenges for day-to-day medical practice. In some hospitals face-to-face clinic consultations have significantly reduced, being replaced by virtual clinics where possible. We hypothesised that virtual follow up of many of our Hypertrophic Cardiomyopathy (HCM) patients could continue indefinitely without impacting on the quality of clinical care, with the overall benefits of maintaining patient safety and convenience, and reduced costs for the hospital. Purpose: The purpose of this study was to evaluate physician consultations in our HCM clinic prior to the COVID-19 pandemic to determine what proportion of consultations resulted in patients developing new symptoms or requiring medication changes. We further looked to see if we could identify any patient factors that would allow us to predict which patients would be most suitable for future virtual follow up. Methods: We retrospectively reviewed the electronic patient records of HCM patients seen in the dedicated Inherited Cardiac Conditions (ICC) clinic for follow-up over a 6-month period in 2018. Patients were classified into high (≥6%), moderate (4-5.9%) and low (<4%) risk groups according to ESC-SCD risk score. Transthoracic echocardiogram and cardiac magnetic resonance features were reviewed. The outcome comprised number of patients developing new symptoms or requiring medication change, as well as hospital admissions for cardiovascular reasons (e.g. angina, arrhythmia, and heart failure) in the 2-years following clinic consultation. Results: Forty-seven HCM patients (mean age 61.4 ± 12.2, 55% male) were identified and reviewed from the ICC clinic. Overall, 36% of patients had interventions from the face-to-face clinic; with 21% of patients developing new symptoms and 32% of patients requiring medication changes. There were 38 low-risk, 4 moderate-risk and 4 high-risk patients. 1 patient was not eligible for the risk stratification due to age over 80. 21% of low-risk, 25% of moderate-risk and 25% of high-risk patients developed new symptoms ( table 1 ) . Over 50% of patients who had a moderate-high ESC-SCD risk score or echocardiographic evidence of systolic/diastolic impairment required medication changes ( table 1 & 2 ) . Only 2 patients had hospital admissions for cardiovascular reasons in the 2-year follow up period, and those with systolic/diastolic impairment also incur high rates of admissions ( table 2 ) . Conclusion: About 60% of HCM patients from our inherited conditions clinic were asymptomatic and did not require changes in medication, which suggests that this group would be very suitable for virtual follow-up clinic appointments post-pandemic. Potential predictive factors would include patients with low ESC-SCD risk score and without left ventricular impairment. Hospital costs may be reduced whilst maintaining patient safety and convenience. HCM patient satisfaction with virtual consultations would be a further area to examine in relation to this. Conflict of Interest: None